2012
DOI: 10.2308/atax-50246
|View full text |Cite
|
Sign up to set email alerts
|

Schedule UTP: Stock Price Reaction and Economic Consequences

Abstract: In 2010, the Internal Revenue Service (IRS) announced the requirement to disclose uncertain tax positions (UTP) on a new schedule (Schedule UTP) to be filed with federal corporate income tax returns. Schedule UTP could increase a firm's tax burden by providing a roadmap for the IRS to identify firms' tax-planning strategies. We find that stock returns around the development of Schedule UTP are negative, consistent with investors' concern that Schedule UTP would impose costs on firms. However, we document a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…As investors have to rely on the information available on the event date to estimate banks' tax aggressiveness, we use the 2011 financial statements to calculate the ETR. This approach is consistent withAbernathy et al (2013).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…As investors have to rely on the information available on the event date to estimate banks' tax aggressiveness, we use the 2011 financial statements to calculate the ETR. This approach is consistent withAbernathy et al (2013).…”
supporting
confidence: 84%
“…Prior studies have demonstrated the importance of considering multiple event dates, especially when investigating a legislative procedure (Donohoe & McGill, 2011;Abernathy et al, 2013;Chen, 2017). For this reason, we extend our analysis by two additional events, although noting some caveats regarding these dates.…”
Section: Additional Event Datesmentioning
confidence: 99%
“…Our study contributes to the literature in two ways. First, prior research has generally investigated the short-term effects of these three disclosure requirements on firm behavior (e.g., Blouin et al, 2010;Donohoe and McGill, 2011;Robinson and Schmidt, 2013;Abernathy, Davenport, and Rapley, 2013;Towery, 2016). What remains unclear is whether the short-term changes in behavior (if any) have persisted over time.…”
Section: Introductionmentioning
confidence: 99%
“…Although a relatively new measure, UTB has been shown to be promising as a useful proxy of tax planning (Abernathy, 2013). Towery (2012) reports that about 77.9 per cent of the reported uncertain tax positions generated permanent differences (that would affect the ETR), 20 per cent of the filed positions generated temporary differences (that RAF 15,1 would not affect the ETR) and only 2.1 per cent generated both permanent and temporary differences.…”
Section: Utb_nonetr As a Useful Measure Of Tax Planningmentioning
confidence: 99%
“…First, the use of UTB as a measure of tax planning is relatively new (i.e. Abernathy, 2013). However, part of the UTB (i.e.…”
Section: Introductionmentioning
confidence: 99%